Hemolytic activity and protective potential of Lamiaceae plants seed extracts and their bioactive components profiling having potential for functional foods and nutraceutical formulations. (November 2022) - Yasir, Muhammad; Jamil, Nuzhat; Nazir, Arif; Kanwal, Qudsia; Mehr-un-Nisa,; Athir, Naveed; Mustafa, Rahat; Al-Mijalli, Samiah H.; Iqbal, Munawar; Ahmad, Naveed
Abstract: This study was designed to examine phenolic profile and bioactivities of two Lamiaceae species, Salvia moorcroftiana and Ocimum sanctum . Hydrolyzed and non-hydrolyzed seed extracts of both species were screened for their hemolytic and mutagenic effects. Both species were found to be nontoxic to red blood cells (cytotoxicity <4%) and selected bacterial strains (mutagenicity <9%), and were evaluated for their anti-hemolytic and anti-mutagenic potentials. The S. moorcroftiana presented better protection against standard cytotoxic and mutagenic compounds than O. sanctum . Moreover, hydrolyzed extracts of both species depicted superior anti-hemolytic (93.58 ± 2.04% for S. moorcroftiana and 90.78 ± 1.88% for O. sanctum ) and anti-mutagenic potentials (70.24 ± 0.69% for S. moorcroftiana and 64.29 ± 0.69% for O. sanctum ) than those of non-hydrolyzed samples. Chemical characterization by LC-ESI-MS/MS of hydrolyzed extracts of both species indicated the presence of various bioactives such as vanillic acid, quinic acid, gallic acid and myricetin. Hence, it is concluded that both of these species can find potential applications in functional food and nutraceutical formulations. Highlights: Lamiaceae seeds are innovative source of functional foods and nutraceuticals. Bound phenolic could be recovered from plant matrix using acidic hydrolysis. Crude extracts depicted good antioxidant and anti-mutagenic activities. LC-ESI-MS/MS exposed up to eleven phenolic compounds in selected plant species.